Interest and limits of the molecular approach for the study of biogeography and speciation : examples in African tropical Mammals - (:unkn) unknown (My University, 2001)
Among the sciences which study the patterns of diversification and distribution of organisms in space and time, biogeography investigates the history of biota based on organism distributions, and phylogeography focuses on one taxa at the time. Biogeographic studies carried out in tropical areas have led to a series of evolutionary hypotheses about faunal diversification and speciation, such as the refuge, the riverine barrier, and the environmental gradient theories. In the present work, we attempt to test these hypotheses by applying the molecular approach to selected mammalian taxa (Insectivora, Rodentia, and Primates) from tropical Africa. We try to estimate the interests and limits of mitochondrial DNA sequencing, the most widely used molecular technique in evolutionary biology, for addressing questions about faunal evolution. First, we constructed a molecular phylogeny of taxa we intended to use for phylogeographic studies, in order to ascertain their monophyly and calibrate a molecular clock for divergence time estimates. Second, we analysed and compared the phylogeographic patterns of four forest-dwelling small mammal species and one primate super-species. Third, we evaluated the evolutionary processes involved in the speciation of cercopithecine primates, by testing their geographic mode of speciation and reconstructing evolutionary scenarios for some life-history traits. The comparison of our molecular-based phylogenies with other sources of information confirms that gene history is not necessarily the same as organism history. Thus, mitochondrial DNA should be studied in combination with other independent data, such as nuclear genes, morphology, ecology and behaviour. The acquisition of reliable phylogenies is a pre-requisite for the study of speciation. In the case of the Cercopithecini, our results suggest that speciation has been predominantly allopatric and driven by Miocene and Pliocene vicariance ev
Keywords: African Research